Pindolol augmentation of serotonin reuptake inhibitors for the treatment of depressive disorder: a systematic review. - Whale, R; Terao, T; Cowen, P; Freemantle, N; Geddes, J (2010)
UNLABELLED: Adding pindolol to serotonergic antidepressant treatment offers a potential strategy for producing a more rapid onset of action and an enhanced antidepressant effect. This review investigated whether pindolol enhances the efficacy of serotonergic antidepressant treatment in adult patients with depressive disorders at sequential time points up to 6 weeks. SEARCH STRATEGY: Cochrane Collaboration Depression, Anxiety and Neurosis-Controlled Trials Register plus unpublished trial data. STUDY SELECTION: Randomised trials including depressed patients, comparing serotonergic antidepressants + pindolol with serotonergic antidepressants + placebo and using depressive symptom clinical outcomes scales. DATA EXTRACTION: Clinical response at time points up to 6 weeks as defined by >50% depression scale score reduction was extracted for each trial as possible. Eleven studies were identified including unpublished data. The pooled odds ratios for dichotomous response to treatment at time points from 1 to 6 weeks were 2.39 (95% CI 1.40-4.06), 2.39 (1.74-3.29), 1.94 (1.46-2.58), 1.59 (1.16-2.18), 1.42 (0.87-2.31) and 1.28 (0.91-1.81). Time-to-event analysis showed a greater response with pindolol augmentation versus placebo (P = 0.04). There was significant heterogeneity between studies at some time points. Dropout rates did not significantly differ between treatment arms. This review suggests an overall beneficial clinical effect of pindolol augmentation, most clearly up to 4 weeks of treatment.